Conflicted masculinities: understanding dilemmas and (re)configurations of masculinity among men in long-term relationships with female sex workers, in Kampala, Uganda. Issue 6 (1st June 2022) - Mbonye, Martin; Siu, Godfrey; Seeley, Janet
Abstract: This ethnographic study explores the experience of men in long-term relationships with sex workers and their construction of masculine identities in Kampala, Uganda. Data were collected in 2019 and comprise in-depth interviews with 13 male partners and two group discussions of women with long-term male partners. Thematic analysis used an intersectional lens to frame reconfigurations of gender and masculinity in the context of relationships with sex workers. All men had been clients of sex workers before progressing to become long-term partners. We discuss the complex ways in which men participated in value systems of respectability and reputation to (re)configure gender relations that made sense of their long-term relationships with sex workers. Men viewed their relationships with women through the normative lens of traditional masculine roles associated with monopoly over a partner's sexuality, provider and father. However, poverty, HIV, the failure to have exclusive sexual rights over a partner, and the shame associated with sex work intersected and disrupted masculinities. Despite this, men found meaning in these relationships through the woman's commitment to the relationship, her financial support, her help in accessing HIV services, and the children from the relationship, thereby attaining respectability and avoiding a crisis of masculinity.